Balinese Spatial System: Language or Culture Affecting It? - Aryawibawa, I Nyoman; Clifton L. Pye (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The present paper was designed to point out if the practice of Balinese spatial system by its speakers is linguistic or cultural in nature. Several scholars indicated, though not dominantly, that the use of a relative system in Balinese spatial system was observed to be used by their research participants. Other scholars in their studies, employing linguistic and nonlinguistic tasks in the production tasks, nevertheless, found out that an absolute system was largely practiced by their research participants. Additionally, there are also quite recent studies investigating the use of Balinese spatial system by local signers in Bengkala village. The findings pointed out that children and adult deaf subjects consistently used pointing in linguistic tasks. However, the child and adult deaf subjects used absolute responses in nonlinguistic tasks. Cultural and Balinese Hindu religious practices seem to guide the use of spatial systems in Balinese.